Understanding "understanding" in Public Understanding of Science. (October 2018) - Huxster, Joanna K.; Slater, Matthew H.; Leddington, Jason; LoPiccolo, Victor; Bergman, Jeffrey; Jones, Mack; McGlynn, Caroline; Diaz, Nicolas; Aspinall, Nathan; Bresticker, Julia; Hopkins, Melissa
This study examines the conflation of terms such as "knowledge" and "understanding" in peer-reviewed literature, and tests the hypothesis that little current research clearly distinguishes between importantly distinct epistemic states. Two sets of data are presented from papers published in the journal Public Understanding of Science . In the first set, the digital text analysis tool, Voyant, is used to analyze all papers published in 2014 for the use of epistemic success terms. In the second set of data, all papers published in Public Understanding of Science from 2010–2015 are systematically analyzed to identify instances in which epistemic states are empirically measured. The results indicate that epistemic success terms are inconsistently defined, and that measurement of understanding, in particular, is rarely achieved in public understanding of science studies. We suggest that more diligent attention to measuring understanding, as opposed to mere knowledge, will increase efficacy of scientific outreach and communication efforts.